Programa de gestão da manutenção predial para edificações hospitalares da rede de atendimento no município de Fortaleza - Nava Júnior, Manoel Maria Henrique (2007)
This thesis deals with the analysis of the conditions and of the management of issues related to equipment and medical building facilities established in the city of Fortaleza, northeastern Brazil. Theoretical studies were developed based on literature research, and a survey was carried out for the locally selected hospitals. This research focuses on the management systems, structure, organization and human resources concerned with the predictive, preventive and corrective maintenance. The whole cycle of the building was adopted as the approach and scope of this work, from the planning, design, construction and its final occupation. Considering the low level of priority given by the administration of such selected units to maintenance problems, this work concludes with a programme of proposals and recommendations which could be useful not only to those units studied, but to others existing within the chosen municipality. It can also be effective to the qualitative improvement of new hospital facilities from the beginning of their planning stage.